IMPLEMENTASI METODE UMMI DALAM PEMBELAJARAN TAHFIDZ DI TPQ AT-TAQWA DUSUN JURUG DESA JUMAPOLO KECAMATAN JUMAPOLO KABUPATEN KARANGANYAR - Abbas, Ngatmin; Rochmawan, Alfian Eko; Naufal, Muhammad Shidqi; Mubarok, Ardan Rifki; Kinasih, Faza Imany (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
The method is a very important learning component to understand by each teacher. Therefore, the success of learning depends on the teaching ability to implement these methods. Application of the right method will speed up the acquisition of results in students. On the other hand, if the application of a method does not match, the results obtained by the student will be slow to achieve. Ummi's method is the Method introduced how to read the Qur'an with tartil. With the use of the Ummi Methods in the learning of the Qur'an, students will be easier on tahsin and memorizing the Qur'an. The purpose of this study was to determine the application of the Ummi method in the learning of the Qur'an at the TPQ At-Taqwa Hamlet Jurug Village.